Narasi Spasial Dalam Museum Nasional: Analisis Pembentukan Identitas Kebangsaan Melalui Storyline “Menjadi Indonesia” - Punto Wijayanto; Ahmad Zuhdi Allam (PURBAWIDYA, 2026)
Museums function not only as repositories of historical artifacts, but also as representational spaces that participate in shaping narratives of national identity. This study aims to analyze how national narratives are constructed through the spatial organization of exhibition spaces in the curatorial storyline “Becoming Indonesia” at the National Museum of Indonesia. The research adopts a qualitative approach through a case study of the permanent exhibition spaces in Building A of the National Museum of Indonesia. Data were collected through spatial observations of exhibition spaces, analysis of curatorial documentation, and a literature review on museum studies and museum architecture. The findings indicate that the “Becoming Indonesia” storyline functions not only as a curatorial framework but also as a spatial narrative structure that tends to guide visitors’ experiences in understanding the process of nation formation in Indonesia. The arrangement of gallery sequences, visual relationships among collections, and patterns of visitor circulation create a storytelling mechanism that connects archaeological, ethnographic, and historical collections into a coherence narrative about cultural diversity and the historical development of Indonesia. In this way, museum exhibition spaces can be understood as interpretive media that organize visitors’ experiences in reading the relationships between objects, history, and national identity. This study suggests that spatial analysis of exhibition spaces can provide insights into how national museums produce narratives of nationhood through spatial organization and visitor experience. The findings contribute to museum and architectural studies by emphasizing the importance of the spatial dimension in curatorial practices.